The corruption of capitalism: why rentiers thrive and work does not pay - Standing, Guy (London, 2016)
"There is a lie at the heart of global capitalism. Politicians, financiers and global bureaucrats claim to believe in free competitive markets, but have constructed the most unfree market system ever. It is corrupt because income is channelled to the owners of property - financial, physical and intellectual - at the expense of society. This book reveals how global capitalism is rigged in favour of rentiers to the detriment of all of us, especially the precariat. A plutocracy and elite enriches itself, not through production of goods and services, but through ownership of assets, including intellectual property, aided by subsidies, tax breaks, debt mechanisms, revolving doors between politics and business, and the privatisation of public services. Rentier capitalism is entrenched by the corruption of democracy, manipulated by the plutocracy and an elite-dominated media. Meanwhile, wages stagnate as labour markets are transformed by outsourcing, automation and the on-demand economy, generating more rental income while expanding the precariat.The Corruption of Capitalism argues that rentier capitalism is fostering revolt, and concludes by outlining a new income distribution system that would achieve the extinction of the rentier while promoting sustainable growth."